Development of A Web-Based Crossword Puzzles to Teach Arabic Vocabulary in Islamic Junior High Schools/ تنمية الكلمات المتقاطعة على الإنترنت لتعيلم المفردات في المدرسة الثانوية - M. Adnan Al-Faraid Rahaded; Nurul Murtadho; Mohammad Ahsanuddin (Universitas Negeri Malang, 2022)
The purpose of this research is to design crossword puzzles on the Internet (web) to teach Arabic vocabulary in secondary schools and describe its quality. The researcher used the ADDIE method, which consisted of five stages: analysis, design, development, application, and evaluation. The sample in this study were students of class VII and VIII MTs Mambaul Ulum Pakis. The data in this study consisted of two types: quantitative data and qualitative data, and the collection method was a questionnaire. The results of this study are (1) Arabic vocabulary teaching materials have used crossword puzzles on the Internet (web) which can be opened and used via the URL http://ttsBahasaarab-mkbaum.com/. The material used is taken from the Ihsan Cendekia Learning Module for the 2013 Curriculum (k13), and this book is published with the construction of the 2013 Curriculum and published by Citra Mentari, compilers: Zainal Arifi, S.Pd, Dra. Siti Mardhiyyah, Nanang Sholihudin, S, Ag., the material consists of 330 vocabularies, the development of all vocabularies in the form of crossword puzzles and their introduction on the web. (2) The results of the expert assessment of product suitability obtained 92.8 percent, from education materials experts and 87.5 percent from teaching aids experts, while for the results of field experiments obtained 80.9 percent, meaning that this product is very valid and applicable.